(untitled) (Research, Society and Development, 2023)
The Systematization of Nursing Care (SAE) is necessary for better assistance provided by the professional, through theoretical knowledge (scientific-clinical) and the actions developed, enabling an exchange of information about the patient’s condition with other professionals for a unified intervention. It is everyone’s right to have dignity and independence in their lives, with rehabilitation being the cornerstone of social reintegration, recovery and physical, mental and general health. The objective was to report the experience of a victim of Spinal Cord Trauma (TRM) using the Systematization of Nursing Care in the rehabilitation service. The scope of this work was a case report and bibliographical review of an exploratory, descriptive nature, with qualitative methods and techniques. A questionnaire consisting of 19 questions was used, created and validated by the authors according to the outlined theme and answered by the person being researched to obtain the necessary information. As a final opinion of this research, the protagonism and essential role of nursing as a member of the multidisciplinary team facing a victim of TRM was highlighted, in which procedural and care management is used in line with clinical reasoning supported by the scientificity of the Systematization conferred in current legislation, in order to provide holistic and effective recovery.